2018
DOI: 10.1177/1055665618767421
|View full text |Cite
|
Sign up to set email alerts
|

The Implications of Nasal Substitutions in the Early Phonology of Toddlers With Repaired Cleft Palate

Abstract: The presence of nasal substitutions following palatal surgery was not always an early sign of VPD. These substitutions were present in the early lexicon of children with and without cleft palate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…These findings are at odds with data that have been published in the literature for many years. Although oral stops may not be produced by all babies with cleft palate, many do produce them, albeit not as frequently as they produce low-pressure consonants (Willadsen and Albrechtsen, 2006; Scherer et al, 2008; Hardin-Jones and Chapman, 2018). In a recent study examining the development and resolution of nasal substitutions, Hardin-Jones and Chapman (2018) reported that 47% (16/34) of their participants with unrepaired cleft palate produced one or more oral stops (or other obstruents) prior to palatal surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are at odds with data that have been published in the literature for many years. Although oral stops may not be produced by all babies with cleft palate, many do produce them, albeit not as frequently as they produce low-pressure consonants (Willadsen and Albrechtsen, 2006; Scherer et al, 2008; Hardin-Jones and Chapman, 2018). In a recent study examining the development and resolution of nasal substitutions, Hardin-Jones and Chapman (2018) reported that 47% (16/34) of their participants with unrepaired cleft palate produced one or more oral stops (or other obstruents) prior to palatal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Although oral stops may not be produced by all babies with cleft palate, many do produce them, albeit not as frequently as they produce low-pressure consonants (Willadsen and Albrechtsen, 2006; Scherer et al, 2008; Hardin-Jones and Chapman, 2018). In a recent study examining the development and resolution of nasal substitutions, Hardin-Jones and Chapman (2018) reported that 47% (16/34) of their participants with unrepaired cleft palate produced one or more oral stops (or other obstruents) prior to palatal surgery. If a baby with a cleft is already experimenting with stops in babble, stimulating that same consonant (or other stops) can begin the process of stabilizing the consonant and thus promote earlier use in words following palatal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Seven of the 8 children who produced pharyngeal fricatives produced them in combination with other atypical patterns of articulation. Previous research has demonstrated that nasal substitutions that are evident in a child’s early phonology are more often associated with delayed emergence of stops than VPD (Hardin-Jones & Chapman, 2018) and backing errors have been associated with positive histories of otitis media with effusion (OME) (Shriberg et al, 2003). Further, as hypothesized by Zajac (2015), while children with cleft palate may be more likely to develop nasal fricatives than children without clefts, both groups may develop this atypical pattern of articulation for the same underlying reason—“fluctuating conductive hearing loss that drives acceptance of nasal frication as auditory targets for oral fricatives” (p. 24).…”
Section: Final Commentsmentioning
confidence: 99%
“…[15][16][17] Lack of emergence of stop consonants following palatal surgery has long been considered an important indicator of the need for early intervention and/or additional surgical management for velopharyngeal dysfunction (VPD). Recently, Hardin-Jones and Chapman 14 examined the relationship between nasal substitutions in early words (identified in language samples obtained at 13, 17, 21, and 27 months of age) and hypernasality at 39 months of age for 34 children with repaired cleft palate. In their retrospective study, they identified the earliest age at which each child produced at least 10 words and then examined words in that sample for the presence of nasal substitutions.…”
Section: Introductionmentioning
confidence: 99%
“…1,6,10–13 In their series of investigations, however, Chapman and colleagues reported that while children in the cleft group produced significantly fewer oral stops than their noncleft peers prior to palatal surgery, 1 more than 60% of these children had one or more obstruents in their phonetic inventory. 14 In their 2018 report, Hardin-Jones and Chapman 14 acknowledged that while some toddlers produce oral stops prior to palatal surgery, the relatively low frequency of these consonants could explain the preference that these children show for words beginning with sonorants. “The preference for words beginning with sonorants in their early lexicon was probably related to the practice and refinement of these types of consonants in babble—and not necessarily to the presence or absence of oral stops per se” (p. 7).…”
Section: Introductionmentioning
confidence: 99%